The Sustainable and Green Management of Spent Lithium-Ion Batteries Through Hydroxy Acid Recycling and Direct Regeneration of Active Positive Electrode Material: A Review - Ambar B. Shrestha; Ananda S. Amarasekara (Batteries, 2025)
The rapid increase in use of lithium-ion batteries in energy storage together with limited supply of critical metals used in batteries and environmental concerns have led to the urgent need for sustainable recycling technologies for these batteries. Li-ion battery chemistry, components, various designs, and two main approaches for recycling: pyrolysis and hydrometallurgical techniques are discussed in this review focusing on the novel, sustainable green approach of hydroxy acid leaching followed by a direct regeneration technique. This two-step emerging technique is compared with other conventional recycling methods in this critical review emphasizing simplicity and commercial potential. Current literature reporting rapid developments on this scalable process with pretreatment phases of sorting, discharging, disassembly of batteries, separation of electrode coatings from current collectors, leaching black mass with hydroxy carboxylic acids, separation of graphite, adjustments of Li, Ni, Mn, and Co compositions, and regeneration via co-precipitation or sol–gel formation techniques followed by pyrolysis are discussed in the detailed review. The conclusion section of this direct regeneration focused critical review gives an insight into challenges in hydroxy acid recycling and direct regeneration technology and practical solutions that may help in development into a mainstream technology.